Analysis of Critical and Creative Thinking Aspects in The Science Textbook of Merdeka Curriculum Materials of Measurement in Scientific Work - Lintang Auliya Kurdiati (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
This study aimed to identify the elements of critical and creative thinking in the Measuring Merdeka High School Curriculum in Science textbooks. This research uses a qualitative descriptive research type. The data source was the Science textbook for SMA Class X Merdeka Curriculum. The instrument used in this research is the researcher as the main instrument. This research's supporting agents are data collection and analysis guides. The data collection procedure in this study was to use documentation techniques. This study's stages of data analysis include data reduction, data presentation, and conclusion. The results showed that the Merdeka High School Curriculum Science textbook on Measurement in Scientific Work contains four elements of critical thinking and seven elements of creative thinking. This research implies that future results of this study can be used as reference material and references in further research